2011
DOI: 10.1074/jbc.m110.211540
|View full text |Cite
|
Sign up to set email alerts
|

Liver-enriched Inhibitory Protein (LIP) Actively Inhibits Preadipocyte Differentiation through Histone Deacetylase 1 (HDAC1)

Abstract: The CCAAT/enhancer-binding protein ␤ (C/EBP␤) is expressed as three isoforms (LAP*, liver-enriched activating protein (LAP), and liver-enriched inhibitory protein (LIP)) that differentially regulate gene expression. The interplay between LAP*, LAP, and LIP in regulating cellular processes is largely unknown, and LIP has been largely regarded to repress transcription through a passive heterodimerization-dependent mechanism. Recently, we have shown that p300/GCN5 and mSin3A/HDAC1 differentially regulate the abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 30 publications
4
32
0
Order By: Relevance
“…C/EBPβ interacts with mSin3a/HDAC through a small AAGF motif between CR6 and CR7. This motif is located in the Nterminal extreme of LIP and mSin3a/HDAC recruitment is in fact an important mechanism of transcription inhibition by LIP (Abdou et al 2011). The association between C/EBPβ and mSin3a/HDAC1 can be decreased by C/EBPβ acetylation at lysines K98, K101 and K102 (Wiper-Bergeron et al 2007).…”
Section: Interaction Of the Cr1 Domain Of Full With Swi/snf And Mediamentioning
confidence: 95%
See 1 more Smart Citation
“…C/EBPβ interacts with mSin3a/HDAC through a small AAGF motif between CR6 and CR7. This motif is located in the Nterminal extreme of LIP and mSin3a/HDAC recruitment is in fact an important mechanism of transcription inhibition by LIP (Abdou et al 2011). The association between C/EBPβ and mSin3a/HDAC1 can be decreased by C/EBPβ acetylation at lysines K98, K101 and K102 (Wiper-Bergeron et al 2007).…”
Section: Interaction Of the Cr1 Domain Of Full With Swi/snf And Mediamentioning
confidence: 95%
“…C/EBPδ has also been able to recruit and transactivate through CBP/p300 A c c e p t e d M a n u s c r i p t 25 (Chamberlain et al 2012;Wang et al 2006), residues Leu81 and Phe82 of C/EBPδ being critical for this interaction (Kovacs et al 2003) C/EBPβ also interacts with the complex formed by the co-repressor mSin3a and the histone deacetylase HDAC. This interaction, particularly with HDAC1, leads to repressed transcription of many genes, including C/EBPα (Abdou et al 2011;WiperBergeron et al 2003), p53, sirtuin 1 and glycogen synthase kinase 3β GSK3β Jin et al 2011;Jin et al 2009), PPARβ (Di-Poi et al 2005 or microglial CD200R1 (Dentesano et al 2012). Interaction of C/EBPδ with mSin3a/HDAC also inhibits transcription (Turgeon et al 2008).…”
Section: Interaction Of the Cr1 Domain Of Full With Swi/snf And Mediamentioning
confidence: 97%
“…Glucocorticoids have been shown to affect the adipocyte differentiation process by up-regulating the expression of C/EBP␦, down-regulation of preadipocyte factor 1, up-regulation of transcription factors such as Forkhead box protein O1 and Kruppel-like factor 15, and through the up-regulation of C/EBP␣ (6 -11). We have reported that Dex treatment activated the transcriptional activity of C/EBP␤ at the C/ebp␣ promoter and increased adipogenesis (12)(13)(14)(15). Furthermore, it has been shown by us and others that the transcriptional potential of C/EBP␤ at the C/ebp␣ promoter is regulated by its acetylation status on critical residues (12,16) and its ability to release the inhibitory mammalian switch-independent 3A (mSin3A)/histone deacetylase (HDAC)1 complex through important regulatory domains (12,14,15).…”
mentioning
confidence: 94%
“…Mutational analyses performed by other groups have demonstrated that substitutions of these amino acids compromise the ability of HDAC1 to deacetylate its substrates (22,30,31). HDAC1 has been implicated in a number of transcriptional processes and has been shown to interact directly and indirectly with a number of transcription factors such as p53, retinoblastoma protein, and C/EBP␤ and C/EBP␦ (13,14,(32)(33)(34). The role of HDAC1 in adipogenesis is somewhat controversial.…”
mentioning
confidence: 96%
See 1 more Smart Citation